PENINGKATAN KEMAMPUAN MEMAHAMI TEKS NARATIVE DENGAN METODE LEARNING BY DOING DI MASA PANDEMI SECARA DARING - MIFTAHUL HIDAYAH (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2021)
The COVID-19 pandemic has forced the world of education to change its system and use a new paradigm to deal with emerging problems. The government made a policy that ratified the independence of learning in the new era. All levels of society must prepare themselves to do face-to-face learning through online activities by utilizing technology within the framework of learning from home. Learning held using online media provides opportunities for students to develop themselves independently, guided by teachers in distance learning (PJJ) through online classes. Many new problems arise, not only faced by students but also by parents and teachers. This is due to not being familiar with PJJ. The problem faced by teachers is that it is difficult to control students let alone make them study seriously and effectively. The problem faced by parents is that not only do they not have the financial ability to provide information technology tools to carry out learning activities but also they do not have sufficient cognitive abilities to assist their sons and daughters in solving problems in lessons, so interesting methods are needed to solve this problem. . English as a foreign language is a big problem for students and parents to carry out learning without direct teacher assistance. Moreover, narrative text is a difficult material for students of SMP Negeri 2 Kepanjen to master. The researcher found that the learning by doing method initiated by Dewey would help students to better understand narrative texts. The researcher tried to apply this method to students in grade 9 ASMP N 2 Kepanjen for the 2020-2021 school year. After applying the method initiated by Dewey, there was a significant improvement in the ability to understand narrative texts. This can be seen from the value they get. The increase in value reached 31.4%. ABSTRAKMasa pandemi covid 19 telah membuat dunia pendidikan harus mengubah sistemnya dan menggunakan paradigma baru untuk menghadapi masalah yang mulai muncul. Pemerintah membuat kebijakan yang mengesahkan kemerdekaan dalam belajar di era baru. Semua lapisan masyarakat harus menyiapkan diri untuk melakukan pembelajaran tanpa tatap muka melalui kegiatan online dengan memanfaatkan teknologi dalam kerangka belajar dari rumah. Pembelajaran di selenggarakan dengan menggunakan media online memberikan kesempatan kepada siswa untuk mengembangkan diri secara mandiri dengan dipandu oleh guru dalam pembelajaran jarak jauh (PJJ) melalui kelas online. Banyak masalah baru yang muncul, bukan hanya dihadapi siswa tapi juga oleh orang tua siswa dan guru. Hal ini disebabkan oleh belum terbiasa dengan PJJ. Masalah yang dihadapi guru adalah sulitnya mengontrol siswa apalagi membuat mereka belajar dengan serius dan efektif. Masalah yang dihadapi orang tua siswa adalah bukan hanya mereka tidak mempunyai kemampuan secara finansial untuk menyediakan perangkat teknologi informasi untuk melakukan kegiatan belajar tapi juga mereka tidak memiliki kemampuan kognitif yang cukup untuk mendampingi putra putrinya menyelesaikan masalah dalam pelajaran, Sehingga metode menarik diperlukan untuk menyelesaikan masalah ini. Bahasa Inggris sebagai bahasa asing adalah masalah besar bagi siswa dan orang tua untuk melakukan pembelajaran tanpa pendampingan guru secara langsung. Apalagi teks naratif adalah materi sulit untuk siswa SMP Negeri 2 Kepanjen kuasai. Peneliti menemukan bahwa metode learning by doing yang digagas oleh Dewey akan membantu peserta didik untuk lebih memahami teks naratif.Peneliti mencoba menerapkan metode ini kepada siswa kelas 9ASMP N 2 kepanjen tahun pelajaran 2020-2021. Setelah menerapkan metode yang digagas oleh Dewey ini ada peningkatan yang cukup signifikan dalam kemampuan memahami teks naratif. Ini bisa di lihat dari nilai yang mereka dapatkan. Kenaikan nilai mencapai 31,4%.